2016
DOI: 10.1039/c6ce01069e
|View full text |Cite
|
Sign up to set email alerts
|

35Cl solid-state NMR spectroscopy of HCl pharmaceuticals and their polymorphs in bulk and dosage forms

Abstract: Herein, we demonstrate the use of 35 Cl solid-state NMR (SSNMR) at moderate (9.4 T) and high (21.1 T) magnetic field strengths for the structural fingerprinting of hydrochloride (HCl) salts of active pharmaceutical ingredients (APIs) and several polymorphs, in both bulk and dosage forms. These include salts of metformin, diphenhydramine, nicardipine, isoxsuprine and mexiletine (the crystal structure of a mexiletine polymorph is reported herein). Signal-enhancing pulse sequences utilizing frequency-swept pulses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 84 publications
3
83
0
Order By: Relevance
“…Usually, the API will be the only component within a formulation that contains chloride anions that can give rise to observable 35 Cl solid‐state NMR signals. Therefore, 35 Cl solid‐state NMR spectra of the tablets are free of interfering excipient signals and allow APIs to be directly interrogated . For example, the DNP‐enhanced static 35 Cl solid‐state NMR spectra of pure crystalline diphenhydramine HCl and of a commercial tablet were identical in appearance, which confirmed that the form of the API was identical in both pure and dosage forms (Figure ) .…”
Section: Applications Of Dnp‐enhanced Solid‐state Nmr Spectroscopy Tomentioning
confidence: 81%
See 2 more Smart Citations
“…Usually, the API will be the only component within a formulation that contains chloride anions that can give rise to observable 35 Cl solid‐state NMR signals. Therefore, 35 Cl solid‐state NMR spectra of the tablets are free of interfering excipient signals and allow APIs to be directly interrogated . For example, the DNP‐enhanced static 35 Cl solid‐state NMR spectra of pure crystalline diphenhydramine HCl and of a commercial tablet were identical in appearance, which confirmed that the form of the API was identical in both pure and dosage forms (Figure ) .…”
Section: Applications Of Dnp‐enhanced Solid‐state Nmr Spectroscopy Tomentioning
confidence: 81%
“…Hydrochloride salts in both pure and dosage forms can be studied with 35 Cl solid‐state NMR spectroscopy . 35 Cl solid‐state NMR has previously been applied to differentiate the polymorphs of APIs and detect APIs within formulations . 35 Cl is a highly abundant (natural abundance (NA) = 75.5%) half‐integer quadrupolar nucleus ( I = 3/2).…”
Section: Applications Of Dnp‐enhanced Solid‐state Nmr Spectroscopy Tomentioning
confidence: 99%
See 1 more Smart Citation
“…In this contribution, we extend the BRAIN CP approach to the study of half‐integer nuclei such as 87 Sr (I=9/2) (one notes that very recently, Schurko et al . used also this approach to study pharmaceutical derivatives and their polymorphs by 35 Cl NMR, I=3/2).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been used as a technique for polymorph distinction and in the screening of hydrochloride (HCl)-containing APIs [25][26][27][28] as well as their dosage forms with excipients, which is difficult for other techniques. [29][30] Chlorine SS-NMR has also been used for the characterization of a chloride ion receptor, 21 alkaline earth chlorides (including hydrates) 24,31 and has been used to comment on halogen bonding [32][33][34] and ion dynamics in solids. [35][36] Chlorine SS-NMR has also found applications in the study of materials such as sodalities 37 However, the optimal choice of the cluster for C Q calculations may not be obvious.…”
Section: Introductionmentioning
confidence: 99%